Blueprint: Seed Bomb / Mohd Izwan Abu Bakar, Nuur Aina Farhana Ahmad Rosli and Siti Nurfaten Abu Bakar - Abu Bakar, Mohd Izwan; Ahmad Rosli, Nuur Aina Farhana; Abu Bakar, Siti Nurfaten (2018)
Seeds Bomb has developed a new and unique range of Herbeno plant capsules by carefully selecting and improving the environment and its can reducing spent of living. Potential green thumbs of any ability and the result is a high quality collection of some of the most powerful genetics available with each and every plant in the range maximized fantastic growth potential. Seeds Bomb assures optimum freshness and quality. All seeds are stored in a temperature and humidity controlled environment. Its also can be controlled via Smart phone.